Marine turbine system directly connected to electrical grid: Experimental implementations using a nonlinear and robust control. (1st February 2018) - Dansoko, M.; Nkwawo, H.; Floret, F.; Goma, R.; Diourté, B.; Arzandé, A.; Vannier, J.C.
Abstract: This paper deals with real-time implementations of a nonlinear and robust control applied on a marine turbine system. For the experimental validation which uses real data from Raz de Sein site (Brittany, France), the DC motor drives a wound rotor synchronous generator. A computer pilots this DC motor in order to stand in for the marine turbine behavior. Experimental results show the control successful of both outputs (terminal voltage and speed) making possible direct connection to electrical grid. In addition, we verify the robustness properties of the complete system under hard mechanical and electrical perturbations. Finally, a comparative study highlight the proposed control performances compared with conventional AVR-PSS which is one of the most widely adopted controller in industry for electrical grid stabilization. Highlights: Two output control (terminal voltage and frequency) via single input (synchronous generator excitation). DC motor is controlled in order to reproduce marine turbine behavior. Experimental validation of sliding mode control for marine turbine connected to electrical grid. Robustness test (simulation and practice) to evaluate the performances of proposed control.